Behavioral changes and gene profile alterations after chronic 1, 950‐MHz radiofrequency exposure: An observation in C57BL/6 mice. Issue 11 (28th August 2020) - Jeong, Ye Ji; Son, Yeonghoon; Choi, Hyung‐Do; Kim, Nam; Lee, Yun‐Sil; Ko, Young‐Gyu; Lee, Hae‐June
Abstract: Introduction: Due to public concerns about deleterious biological consequences of radiofrequency electromagnetic fields (RF‐EMF), the potential effects of RF‐EMF on the central nervous system have received wide consideration. Methods: Here, two groups of C57BL/6 mice, aged 2 and 12 months, were exposed to 1, 950‐MHz RF‐EMF at a specific absorption rate of 5.0 W/kg for chronic periods (2 hr/day and 5 days/week for 8 months). Behavioral changes were then assessed in the mice at 10 months (sham‐ or RF‐10M) and 20 months (sham‐ or RF‐20M), on the open‐field test, the Y‐maze test, and an object recognition memory task, while biological effects were analyzed via microarray gene profiling of the hippocampus. Results: Open‐field test results showed a decrease in the time duration spent at the center while there was a decrease in enhanced memory shown by the Y‐maze test and the novel object recognition test in the RF‐20M mice, compared to sham‐exposed mice, but no significant changes in the RF‐10M group. Based on a 2‐fold change cutoff, the microarray data revealed that 15 genes, which are listed as being involved in neurogenesis on Gene Ontology, were altered in both groups. Quantitative real‐time PCR for validation showed increased expression of Epha8 and Wnt6 in the hippocampi of RF‐20M group mice, although 13 additional genes showed no significant changes following RF‐EMF exposure. Conclusion: Therefore, cognitive enhancement following chronic exposure for 8 months to RF‐EMF from middle age may be associated with increases in neurogenesis‐related signals in the hippocampus of C57BL/6 mice. Abstract : Young‐ and middle‐aged C57BL/6 mice, aged 2 and 12 months, were exposed to 1, 950‐MHz RF‐EMF at an absorption rate of 5.0 W/kg for 2 hr/day and 5 days/week for 8 months. We found an association between chronic RF‐EMF exposure‐induced behavioral improvement and hippocampal gene signature in middle‐aged mice.